Use of genetic markers to build a new generation of Eucalyptus pilularis breeding population - Da Silva, P. H.M.; Shepherd, M.; Grattapaglia, D.; Sebbenn, A. M. [UNESP] (My University, 2015)
Tree improvement generally proceeds by incremental gains obtained from recurrent selection in large diverse populations but is slow due to long generation times and delay till trees reach assessment age. This places a premium upon extracting data from historic introductions used to found landraces when reinstating modern breeding programs. The value of such resources, however, may be degraded due to a lack of records on germplasm origins, pedigrees and early performance, but DNA technology may help recoup some of this value. Eucalyptus pilularis (subgenus Eucalyptus) is regarded as a premier hardwood plantation species for saw log and poles in Australia, but has not been used extensively despite early introductions and testing in many countries overseas. Here we use DNA fingerprinting to assess genetic diversity and inbreeding in historic introductions of E. pilularis to evaluate this resource in advance of a reinvigorated breeding effort for this species in Brazil. As expected, based on the available documentation for the introductions, genetic diversity relative to Australian reference populations does not appear to be compromised, and there was unlikely to be excessive inbreeding. Also, favorable, was the likelihood that further selections should not unduly increase the relationship in the next generation. Interestingly, we note the importance of testing widely adapted sources of germplasm when making introductions, as provenances which performed poorly in tests on productive sites in Australia, may have value when matched with lower fertility sites overseas.
Keywords: Blackbutt; Genetic diversity; Growth; Pedigree information; Relatedness